The Influence of Doctors' Knowledge and Attitudes on the Behavior of Filling Out the Cause of Death - Reza Fajriyani; Ambarwati (Media Informasi, 2026)
The Death Certificate Form is an essential component of medical records, serving clinical, administrative, legal, and policy-making purposes. Incomplete or inaccurate completion of this form may affect mortality statistics, insurance claims, and hospital management decisions. This study aimed to analyze the influence of doctors’ knowledge and attitudes on their behavior in completing the cause of death form at Permata Cirebon Hospital. This quantitative study employed a cross-sectional design and was conducted from January to February 2025. The study population consisted of all inpatient attending physicians at Permata Cirebon Hospital, with a total sample of 45 doctors selected using a total sampling technique. Data were collected through observation checklists and structured questionnaires. Statistical analysis included descriptive analysis, classical assumption tests, and multiple linear regression. The results showed that most respondents had good knowledge (75.6%) and positive attitudes (71.1%) toward completing the cause of death form. However, multivariate analysis indicated that knowledge (p = 0.307) and attitude (p = 0.095) did not have a significant effect on completion behavior, either partially or simultaneously (F = 1.654; p = 0.204). These findings suggest that factors beyond knowledge and attitude, such as workload, documentation systems, training, and organizational support, may play a more dominant role in influencing doctors’ behavior. Strengthening institutional support and documentation systems is recommended to improve the completeness of death certificate forms.